Colposcopic Findings among VIA Positive Women: Experience at a Tertiary Care Hospital - Choudhury, Farzana Rabee; Uddin, ABM Zakir; Yusuf, M Abdullah (Journal of Current and Advance Medical Research, 2014)
Background: Visual inspections of the cervix after acetic acid application (VIA) are widely recommended as the method of choice in cervical cancer screening program in resource-limited settings. Objective: The purpose of the present study was to see the status of VIA test result at a tertiary care hospital. Methodology: This cross sectional study was carried out at Shaheed Suhrawardy Medical College, Dhaka and Dhaka Medical College, Dhaka from April 2012 to March 2013 for a period of one year. VIA was performed and colposcopy was done among the VIA positive patients. Results: A total number of 65 VIA positive patients were evaluated colposcopically In all VIA positive patients, colposcopically positive was in 47.7% cases. Among colposcopically positive patients CIN-I was 27.69%; CIN-II was 18.46% and CIN-III was 1.54%. Conclusion: VIA test is positive in a high number of patients which has a great number of abnormalities were found. DOI: http://dx.doi.org/10.3329/jcamr.v1i1.19559 J Curr Adv Med Res 2014;1(1):8-12]